Lipid-lowering and anti-aggregant Allicor activity in patients with moderate hypercholesterolemia - N. I. Gromnatsky; Zh. E. Sereditskaya; N. V. Lazareva (Кардиоваскулярная терапия и профилактика)
Aim. To assess long-term (6 months) Allicor therapy effects on lipid profile, lipid peroxidation (LP), and functional platelet (PL) activity in patients with moderate hypercholesterolemia (HCH). Material and methods. The study included 56 patients with clinically manifested atherosclerosis and 56 patients with at least one risk factor (RF), but with no clinical atherosclerosis manifestation. In both groups, the participants were randomized (28 subjects in every sub-group) to Allicor therapy (300 mg/d) or lipid-lowering diet. After three months of Allicor therapy, in patients with clinically manifested atherosclerosis, the dose was increased up to 600 mg/d. Blood lipid profile, as well as the levels of lipoprotein (a), lp (a), plasma LP products, functional PL activity after adrenaline, ADP, ristocetin, and serotonin stimulation were measured. Results. In both groups, long-term Allicor therapy significantly reduced atherogenic lipid profile changes, LP intensity, and initially enhanced PL activation, increasing PL platelet anti-aggregation, in contrast to diet group. Six-months Allicor therapy did not affect lp (a) levels. Conclusion. Long-term (at least 6 months) Allicor therapy could be recommended as primary and secondary cardiovascular prevention method, normalizing aggregant and anti-aggregant PL activity, as well as lipid metabolism, in patients with moderate HCH.